Economic Behaviour and Welfare Attainment of Independent Smallholder Oil Palm Households in Musi Rawas District - Lifianthi; Rosana, Elly; Mulyana, Andy; Thirtawati (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2025)
This research examines the economic behaviour of independent oil palm smallholders in fulfilling household expenditures from all their income sources and their level of welfare at present and the stability in the future. The income of oil palm smallholders in Megang Sakti District, Musi Rawas Regency, was IDR 24,731,506 per hectare per year. The total income of the farm household was IDR 43,614,839 per year, which was contributed by the oil palm plantation, the non-oil palm plantation, and non-farming productive activities.All household expenditures could be covered by all existing sources of income, and the net future income will increase as the oil palm plantation enters productive age periods. It has been revealed that oil palm plantations operated by independent smallholders present significant opportunities for economic growth and rural development, but they raise challenges related to sustainability, market access, and social equity. The independent oil palm farmers are recommended to (1) form an independent farmer institution and implement proper and sustainable institution management and (2) submit a proposal to the Oil Palm Plantation Fund Management Agency (BPDPKS) and other financial institutions to demand a grant or get a loan at an affordable interest rate for financing their future business activities. Furthermore, there are ten practical actions that can be implemented by the independent oil palm smallholders.